Long-Term Performance of Trestle Bridges: Case Study of an Indonesian Marine Port Structure - Yusak Oktavianus; Massoud Sofi; Elisa Lumantarna; Gideon Kusuma; Colin Duffield (Journal of Marine Science and Engineering, 2020)
A precast reinforced concrete (RC) T-beam located in seaport Terminal Peti Kemas (TPS) Surabaya built in 1984 is used as a case study to test the accuracy of non-destructive test techniques against more traditional bridge evaluation tools. This bridge is mainly used to connect the berth in Lamong gulf and the port in Java Island for the logistic purposes. The bridge was retrofitted 26 years into its life by adding two strips of carbon fiber reinforced polymer (CFRP) due to excessive cracks observed in the beams. Non-destructive field measurements were compared against a detailed finite element analysis of the structure to predict the performance of the girder in terms of deflection and moment capacity before and after the retrofitting work. The analysis was also used to predict the long-term deflections of the structure due to creep, crack distribution, and the ultimate moment capacity of the individual girder. Moreover, the finite element analysis was used to predict the deflection behavior of the overall bridge due to vehicle loading. Good agreement was obtained between the field measurement and the analytical study. A new service life of the structure considering the corrosion and new vehicle demand is carried out based on field measurement using non-destructive testing. Not only are the specific results beneficial for the Indonesian port authority as the stakeholder to manage this structure, but the approach detailed also paves the way for more efficient evaluation of bridges more generally over their service life.